A Note on the Form and Use of the Language of Nias - Wa’özisökhi Nazara (TEKNOSASTIK, 2019)
Like other languages, the language of Nias is a system of communication, a tool for thought, a medium for self-expression, a social institution and ethnic pride among its native speakers. In spite of its important functions, the language Nias reveals some phenomena calling for attention. One of the phenomena has to do with the increase of education and language contact involving the speakers of the Nias language. Another phenomenon has to do with the attitudes of the speakers of the Nias language toward their native language and culture in general. Still another has to do with some government policies, whose significant positive contribution to the Nias language is still debatable. This short article is organized into four parts. The first part the introduction where the background of the writing the article is presented. The second part contains a short description of the form of the language of Nias. The third part is about the use of the language. The last part is the recommendation on preservation and revitalization of the Nias language.